Dignitary Medicine: A Novel Area of Medical Training - Al Mulhim, Mobarak A; Darling, Robert G; Kamal, Hetaf; Voskanyan, Amalia; Ciottone, Gregory (Curēus (Palo Alto, CA), 2019)
Dignitary medicine (DM) involves the provision of healthcare to government leaders and other high-profile individuals collectively referred to as “dignitaries.” Due to the unique circumstances around their lifestyle, dignitaries often receive suboptimal healthcare. We define the requisite skills needed to practice DM based on the available literature and provide a framework for training providers in these skills.A review of the English language medical literature focussing on adult subjects was performed, searching for terms such as “dignitary medicine,” “VIP medicine,” and “protective medicine.” Literature was gathered from CINAHL, Google Scholar, PubMed, EBSCOHost, and San Bernardino County Library databases and then analyzed by experienced DM providers.A total of 23 relevant articles were eligible for review. No meta-analyses on the subject exist. We found that existing studies highlight skills in wellness, executive health, and protective medicine, which form the backbone of DM.The burgeoning field of DM encompasses several disciplines and skills. We strongly recommend a structured curriculum for the field of DM, focused on dignitary wellness, executive health, and protective medicine.